THEORETICAL ANALYSIS OF APPROACHES TO ORGANIZATION OF THE INTERACTION OF NEGOTIATION GROUPS OF COUNTRIES ON INTERNATIONAL ENERGY MARKETS - Kis, H. R.; Bnо-Ayrian, M. K. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
Based on the theoretical analysis of possible options for interaction between the parties to international negotiation processes, presented in the form of a typical negotiating pair, namely a system of two functional units, negotiating groups from the parties, each of which can use well-known searching and decision-making technologies to achieve mutually beneficial and mutually acceptable solutions in the absence of the Best Alternative To a Negotiated Agreement (BATNA), the article demonstrates that the results of interaction and negotiations between two independent functional units depend on the value of so-called coefficients of their subjectivity calculated as a ratio of the number of objects of its influence to the number of subjects in the system of public administration, which can influence the behaviour and decisions of the group. The article proves that in the absence of the Best Alternative To a Negotiated Agreement (BATNA), the subjectivity coefficients of the parties should be approximately equal. It demonstrates that the subjectivity of national negotiation groups in the field of energy diplomacy is low and determines that an increase in the level of their subjectivity can be facilitated through the establishment of a specialised energy diplomatic structure subordinate to the Presidential Administration of Ukraine, which will hire specialists with professional diplomatic education and experience in the field of the national economy energy provision, thus minimising the influence of the factors aimed at a deliberate deformation of the latter in favour of foreign strategic players, corruption schemes of internal business structures, their associations, etc. on the national energy diplomacy and the concluded international treaties.